Hepatoprotective Activity of Ethanolic Leaves Extract of Vachellia origena (Hunde) Kyal. and Boatwr. (Fabaceae) on Paracetamol-Induced Hepatotoxicity in Male Guinea Pigs - Kaidama, Warda Mohamed A.; Al-Matari, Osamah E.A.; Ayoon, Abdullah A.M.; Qshnoon, Abdulaziz M.N.; Al-Sahlah, Ahmed M.A.; Yassin, Ahmed Y.A.; Raheb, Hassan A.J.; Aklan, Hassan A.G.; Ali, Mohammed A.M.; Hunaish, Mohammed F.S.; Al-Ahmadi, Osama A.M.; Al-Hothaivi, Rafat H.A.; et al. (PSM Biological Research, 2025)
Vachellia origena is a tree distributed in J. Saber, Alturba, Ibb, Dhamar, Sanaa, Haraz, Shibam, and Yafea. They have antibacterial, antifungal, and antioxidant properties. This study aimed to investigate the effect of V. origena ethanolic leaves extract on biochemical parameter activities and histopathological changes of the liver induced by paracetamol in male guinea pigs. A total of 28 male guinea pigs (350-650 g) were randomly assigned to seven groups of five guinea pigs each. Group I served as the control group. Group II received PCM (500 mg/kg) alone, Group III received PCM and proximol (0.8 mg/kg), Group IV received 100 mg/kg V. origena leaves extract alone, and Group V received 200 mg/kg V. origena leaves extract alone. Group VI was administered PCM (500 mg/kg) and 100 mg/kg of V. origena leaves extract. Meanwhile, group VII was administered with PCM (500mg/kg) and 200 mg/kg of V. origena leaves extract. The treatment period lasted for ten days, after which sera were harvested and assayed for serum liver indices using standard methods. The data obtained indicated that blood AST, ALT, ALP, and total bilirubin levels were elevated in the PCM-only group. It also resulted in a number of histopathological alterations. Treatment with the ethanolic leaf extract of V. origena (100 mg/kg and 200 mg/kg) reduced the amount of histopathological lesions in guinea pigs and shielded the liver from PCM-induced intoxication. Data from our study suggest that the ethanolic extract of the leaves of the plant V. origena has protective effects against PCM-induced liver toxicity.